Relevance of the GH-VEGFB/VEGFA axis in liver grafts from brain-dead donors with alcohol-associated liver disease - Micó-Carnero, Marc; Rojano-Alfonso, Carlos; Maroto-Serrat, Cristina; Cutrin, Juan Carlos; Casillas-Ramírez, Araní; Peralta, Carmen (Frontiers in Cell and Developmental Biology, 2025)
IntroductionGrafts with alcohol-associated liver disease (ALD) subjected to prolonged cold ischaemia from donors after brain death (DBD) are typically unsuitable for transplantation. Here, we investigated the role of growth hormone (GH) in livers with ALD from DBDs and its relationship with vascular endothelial growth factor A (VEGFA) and VEGFB.MethodsLivers from rats fed ethanol for 6 weeks and with brain death (BD) were cold stored for 24 h and subjected to ex vivo reperfusion. Hepatic damage and proliferative and inflammatory parameters were analysed after BD, before graft retrieval, and after reperfusion. Survival was monitored using an in vivo transplantation model.ResultsIn DBDs, the administration of GH, which increased the levels in the intestine but not in the liver, induced the generation of both VEGFA and VEGFB in the intestine and protected against hepatic damage caused by BD before retrieving liver grafts from donors. However, VEGFA was the only factor that protected against damage after cold ischemia and reperfusion, which also increased the survival of the recipients.DiscussionIn conclusion, the signalling pathway and beneficial properties of the GH-VEGFA/VEGFB pathway, in which the intestine-liver axis plays a key role, were disrupted when grafts with ALD from DBDs were retrieved from donors and subjected to cold ischemia and reperfusion.